Production quality improvement during manufacturing systems ramp-up. (November 2018) - Colledani, M.; Tolio, T.; Yemane, A.
Abstract: In the current manufacturing context, characterized by short product life-cycles, large product variety, product customization and short innovation cycles, achieving target production quality performance is challenging, especially due to the frequent ramp-up phases the system undergoes along its life-cycle. Available production quality methods focus on high-volume productions and long-term system performance, while they lose effectiveness during the system ramp-up, where instability and unknown disturbances affect the system dynamics. This paper proposes a reference framework for improving production quality performance during the system ramp-up phase. Two strategies for properly dealing with this problem are discussed, consisting in anticipating ramp-up problems during the design phase and performing continuous improvement of production quality performance measures during the system ramp-up. The most effective approaches following these strategies are revised and future research directions in this new research area are drawn.